Postmodern Episteme of Power and its Outlines in Public Discourse in Lithuania - Baločkaitė, Rasa (Sociologija. Mintis ir veiksmas, 2005)
The aim of this article is to analyze the postmodern episteme of power and its outlines in Lithuania. Postmodern concept of power and discursive regime of truth is analyzed following the theoretical premises of poststructuralist theories by J.–F. Lyotard and J. Baudrillard. Credibility of postmodern discourse in Lithuania is being proved by illuminating and developing the concept of double modernization of Lithuania and devaluation of two projects of modernity, the soviet one and the national one. The model of national modernity replaced the devaluated model of soviet modernity in Lithuania after 1990. The national modern system of signs and symbols, inherited partly from early twentieth century, experienced a deep crisis in approximately 1993: credibility and implied self evidence of the meta language of national rebirth has been destroyed; systematic exploitation of remains of the meta language, its signs and symbols, turned out to normative and commercially successful activity; and finally parody, former shadow of reality, overshadowed the reality itself. The postmodern discursive regime of truth and power emerged in Lithuania from the crisis of modern meta language of national rebirth.